New Approaches in Teaching Dialogue in High School From Position of Updated Program (Journal of Educational Sciences, 2020)
The purpose of this article is to summarize the theoretical experience and practical application of interactive learning through active methods in higher education in Kazakhstan. In high schools there is a full-fledged mastering and active use in the classroom of new strategies and methods of learning according to the updated program. An attempt is made to characterize the active teaching methods used in the classroom. Active learning methods contribute to the development of student communication skills, form the ability to argue their point of view. The hypothesis of this article is that we use the methods used in the classroom as teaching methods that encourage not only thinking, but also practical activity of the student. Interactive learning is one of the popular methods for the development of students’ speech in groups with the Kazakh language of instruction. It is proposed to teach the dialogue on the types of conversations – cumulative, research, and discussion-debates, using the reception of questions on Bloom’s daisy, to justify his own point of view, the PSM strategy is proposed. he types of work that contribute to the development and improvement of the ability to formulate thin and thick questions are shown. The article describes pedagogical methods for mastering critical thinking, creating a collaborative environment in a group. Key words: dialogue, dialogue learning, cumulative conversation, research conversation, conversation-debate.